Student’s satisfaction of centralised parking system in UiTM Shah Alam / Norhasanah Romli - Romli, Norhasanah (Faculty of Architecture, Planning and Surveying, 2013)
Parking is important to vehicle user in everywhere they are going. For example to public area, school, university and others. There are many types of parking system, and one of them is centralized parking system. Parking is important and should be highlighted by management because without the parking, user cannot park their vehicle at suitable area to go to the place for any dealings. That's why the provision of adequate parking by the management is important to make sure there are enough parking space to the users. Facilities management is responsible in providing adequate parking to facilitate the user. Study was carried out to identify student’s satisfaction level toward the centralized parking that provided by the management. The objectives of this study are to study the management of centralized parking system in UiTM Shah Alam, to identify problems of centralized parking system in UiTM Shah Alam, and to recommend the improvement of facilities for satisfaction of user to use the centralized parking. There are three method used to obtain the primary data and the method were done are by distributing the questionnaire to centralized parking users, interview was carried out to the management consist of UiTM Facilities Management, UiTM Police’s staff and UiTM Vehicle’s staff and by observation with take the photo and write a short note. For secondary data, it was collected with data that have been published and collection of previous researcher. Apart from that, research also carried out on the needs and expectation of the users towards the centralized parking. The finding revealed, the users were still not satisfied with the parking system and facilities provided at the parking. Thus, it clearly shows that management concerned need to undertake measures to improve and develop an integrated plan for the existing centralized parking system.